2019
DOI: 10.1002/mp.13263
|View full text |Cite
|
Sign up to set email alerts
|

Part II: Verification of the TrueBeam head shielding model in Varian VirtuaLinac via out‐of‐field doses

Abstract: Purpose A good Monte Carlo model with an accurate head shielding model is important in estimating the long‐term risks of unwanted radiation exposure during radiation therapy. The aim of this paper was to validate the Monte Carlo simulation of a TrueBeam linear accelerator (linac) head shielding model. We approach this by evaluating the accuracy of out‐of‐field dose predictions at extended distances which are comprised of scatter from within the patient and treatment head leakage and thus reflect the accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Leakage dose at 100 cm away from primary beam was <0.1% of the CAX dose, thus meeting the acceptance criteria specified by AAPM TG 45 . The comparison of these measurements to TrueBeam head shielding model‐based Monte Carlo simulations from Varian VirtuaLinac will be published separately …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Leakage dose at 100 cm away from primary beam was <0.1% of the CAX dose, thus meeting the acceptance criteria specified by AAPM TG 45 . The comparison of these measurements to TrueBeam head shielding model‐based Monte Carlo simulations from Varian VirtuaLinac will be published separately …”
Section: Discussionmentioning
confidence: 88%
“…34 The comparison of these measurements to TrueBeam head shielding model-based Monte Carlo simulations from Varian VirtuaLinac will be published separately. 35 Kry et al 23 reported in-plane measurements for 6X beams for Varian C-series linac dose for 4 9 4 cm 2 , 10 9 10 cm 2 , and 20 9 20 cm 2 out to a distance of 55 cm from CAX are given in Fig. 2 of their paper.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study using Monte Carlo simulations, Wijesooriya, et al reported that out-of-field doses reduced exponentially with distance. 19 Overall, these results demonstrate the feasibility of using OSLDs for low-scattered radiation measurements.…”
Section: Discussionmentioning
confidence: 56%
“…2 Outof -field MC simulations should be validated through measurements. 2,11 Recent investigations by our group 12 have reported a remarkable sensitivity of the glow curve of the TLD material CaF 2 :Tm, called TLD-300, to photon energy in the range encountered in diagnostic radiology applications. Previously, this feature had been mostly studied as a function of the radiation quality of ion beams.…”
Section: Introductionmentioning
confidence: 99%